Англо-русский словарь по телекоммуникациям: ок. 34000 терминов / А. В. Александров - Александров Александр Валерьевич (РУССО, 2004)
Экземпляры: ИН (20070116) / Инвентарный номер: 1060780 / Цена: 549.24 / Сис.шифр: 81.432.1-4 / Авт.знак: А 46 / ГРНТИ: 16 / ББК: 81.432.1-43